2011
DOI: 10.4236/ajac.2011.22013
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Dissolved Trace Nickel in Environmental Waters by On-Line Sonodigestion-Flow Injection Solid Phase Extraction Coupled to Flame Atomic Absorption Spectrometry

Abstract: A simple on-line sonodigestion system was successfully used for breakdown organic nickel complexes in environmental waters acidified with diluted nitric acid prior to flow injection total dissolved nickel preconcentration in a microcolumn containing a chelating resin (Chelite Che with iminodiacetic acid groups) and determination by flame atomic absorption spectrometry. For the determination of the dissolved labile nickel fraction, microcolumns packed with the chelating resin were loaded in-situ with the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…This scheme is represented with permission from reference no. 53 . Copyright SciRes 2011 (http://www.SciRP.org/journal/ajac).…”
Section: Nickel Toxicity In Plantsmentioning
confidence: 99%
See 3 more Smart Citations
“…This scheme is represented with permission from reference no. 53 . Copyright SciRes 2011 (http://www.SciRP.org/journal/ajac).…”
Section: Nickel Toxicity In Plantsmentioning
confidence: 99%
“…A study in hens revealed that nickel exposure decreased the magnesium, manganese, and zinc levels in various tissues. 53 According to studies, nickel and zinc had antagonistic effects on animals and humans. 36 In addition to its cancer-causing properties, nickel can also cause sensitization reactions in humans (Scheme 2).…”
Section: Nickel Toxicity In Humans and Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several procedures for samples pretreatments have been developed including; solid phase extraction [8][9][10][11], cloud point extraction [12], dispersive liquid-liquid microextraction [13,14]. In addition, an online sonodigestion method was applied to extract nickel from water samples before the analysis by flame atomic absorption spectrometry [15].…”
Section: Introductionmentioning
confidence: 99%